Kajian Sistem Pencernaan Hewan Invertebrata dan Vertebrata - Nurzahra Adelia Putri; Imelia Ada’; Riska Dwiyanti; Ainun Mardhiyah; Sahribulan Sahribulan (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The digestive system is a system that breaks down complex components into simpler ones so that they are easily absorbed by the body's cells. The structure of the digestive organs of each animal varies depending on the level of cell organization and the type of food the animal eats. The aim of this article is to examine the digestive system in invertebrate and vertebrate animals. This article was created using the literature review method. Based on the results of a review of literature on the digestive system of invertebrate animals, at the lowest phylum level, the digestive organs are in the form of gastrovascular cavities formed in protozoa, porifera and coelenterates, at the higher level, namely platyhelminthes, nemathelminthes, annelids, molluscs, arthropods and echinoderms, the digestive organs are recognizable. Vertebrate animals such as fish, amphibians, reptiles, birds and mammals have a more complex digestive system. The vertebrate digestive system consists of the mouth, esophagus, stomach (gestin), small intestine (intestinum tenue), large intestine (intestinum crassum), and anus.